2020
DOI: 10.3389/fmicb.2020.568510
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Antibiotic-Associated Virulence of Pseudomonas aeruginosa Using an ex vivo Lung Biofilm Model

Abstract: Background Bacterial biofilms are known to have high antibiotic tolerance which directly affects clearance of bacterial infections in people with cystic fibrosis (CF). Current antibiotic susceptibility testing methods are either based on planktonic cells or do not reflect the complexity of biofilms in vivo . Consequently, inaccurate diagnostics affect treatment choice, preventing bacterial clearance and potentially selecting for antibiotic resistance. This leads to prolo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Following investigation of quorum sensing gene expression and the implication on efflux pump expression, we aimed to determine whether growth in the EVPL model—with no prior exposure to antimicrobials—resulted in differing expression of antimicrobial resistance (AMR) associated genes. We have previously shown that high levels of antibiotic tolerance are evident in the EVPL model ( 16 ) and clinical infection typically demonstrates much higher resistance to antimicrobial treatment than is predicted in vitro . We looked at the expression of 52 P. aeruginosa PA14 AMR genes, predicted using the Comprehensive Antibiotic Resistance Database (CARD) ( 26 ), in each contrast.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Following investigation of quorum sensing gene expression and the implication on efflux pump expression, we aimed to determine whether growth in the EVPL model—with no prior exposure to antimicrobials—resulted in differing expression of antimicrobial resistance (AMR) associated genes. We have previously shown that high levels of antibiotic tolerance are evident in the EVPL model ( 16 ) and clinical infection typically demonstrates much higher resistance to antimicrobial treatment than is predicted in vitro . We looked at the expression of 52 P. aeruginosa PA14 AMR genes, predicted using the Comprehensive Antibiotic Resistance Database (CARD) ( 26 ), in each contrast.…”
Section: Resultsmentioning
confidence: 98%
“…We have developed an ex vivo pig lung (EVPL) model of the CF lung environment that replicates key phenotypic aspects of P. aeruginosa chronic biofilm infection ( 13 16 ). We aimed to assess the P. aeruginosa transcriptome as biofilm infection establishes in the EVPL model, to determine the extent to which the model accurately replicates P. aeruginosa gene expression during human CF infection.…”
Section: Introductionmentioning
confidence: 99%
“…shown that high levels of antibiotic tolerance are evident in the EVPL model [16] and clinical infection typically demonstrates much higher resistance to antimicrobial treatment than is predicted in vitro. We looked at the expression of 52 P. aeruginosa PA14 AMR genes, predicted using the Comprehensive Antibiotic Resistance Database (CARD) [27], in each contrast.…”
Section: Locus Tagmentioning
confidence: 92%
“…We have developed an ex vivo pig lung (EVPL) model of the CF lung environment that replicates key phenotypic aspects of P. aeruginosa chronic biofilm infection [13][14][15][16]. We aimed to assess the P. aeruginosa transcriptome as biofilm infection establishes in the EVPL model, to determine the extent to which the model accurately replicates P. aeruginosa gene expression during human CF infection.…”
Section: Introductionmentioning
confidence: 99%
“…While there is some utility to pursue the development of non-mammalian models of biofilm-infection such as Drosophila melanogaster , Galleria mellonella or Danio rerio (Zebrafish) ( Lebeaux et al., 2013 ), identification of ex vivo models that recreate the infectious environment should be encouraged. Among recently developed ex vivo models are, for example, an ex vivo pig lung biofilm model used for understanding antibiotic tolerance of P. aeruginosa biofilms ( Hassan et al., 2020 ) or an ex vivo murine skin biopsy model to characterize B. burgdoferi biofilms, the etiological agent of Lyme disease ( Torres et al., 2020 ). Last but not least with the development of reconstituted organs such as organoids or organ-on-a-chip, one could anticipate that adaptations of these models to the understanding of the physiopathology of biofilm infections, interactions of biofilms with the immune response or biofilm behaviors in the presence of antimicrobials would provide important information relevant to biofilms in infectious contexts ( Jimi et al., 2017 ; Choi et al., 2020 ; Yuan et al., 2020 ).…”
Section: Challenges In Methods For Investigating Biofilmsmentioning
confidence: 99%